Statistics and applied quantitative methods for social sciences: a guide for beginners - Abduh, Muhamad (s.n, 2012)
This project aim to help academic staffs and graduate students who do not have quantitative research methods skill by providing them a book as their guidance on how to properly utilize quantitative research methods